2013
DOI: 10.1140/epjb/e2013-40456-9
|View full text |Cite
|
Sign up to set email alerts
|

Burstiness and spreading on temporal networks

Abstract: We discuss how spreading processes on temporal networks are impacted by the shape of their inter-event time distributions. Through simple mathematical arguments and toy examples, we find that the key factor is the ordering in which events take place, a property that tends to be affected by the bulk of the distributions and not only by their tail, as usually considered in the literature. We show that a detailed modeling of the temporal patterns observed in complex networks can change dramatically the properties… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
78
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(78 citation statements)
references
References 28 publications
(36 reference statements)
0
78
0
Order By: Relevance
“…The time series of user activities, e.g., posting a tweet and replying to a message, are quite distinct from uncorrelated (Poisson random) dynamics in the presence of burstiness [18][19][20], temporal correlations [6,21,22], and non-stationarity of human daily rhythm [23,24], which has significant implications. Diffusion on a temporal network cannot be accurately described by models on static networks and consequently the process presents non-Markovian features with strong influence on the time required to explore the system [25,26]. Furthermore, the dynamics drives a strong heterogeneity observed in user activity [27,28] and user/content popularity [29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…The time series of user activities, e.g., posting a tweet and replying to a message, are quite distinct from uncorrelated (Poisson random) dynamics in the presence of burstiness [18][19][20], temporal correlations [6,21,22], and non-stationarity of human daily rhythm [23,24], which has significant implications. Diffusion on a temporal network cannot be accurately described by models on static networks and consequently the process presents non-Markovian features with strong influence on the time required to explore the system [25,26]. Furthermore, the dynamics drives a strong heterogeneity observed in user activity [27,28] and user/content popularity [29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…This effect should be further amended by the effect of triangles or longer cycles, likely leading to a further asymptotic slowdown of the diffusion. This is a new mechanism for the impact of network temporality on diffusive processes, adding to intrinsically different mechanisms such as the bus paradox, where a walker may sit on a node for a very long time [11,19], and the further fact that the mixing time of bursty walker may be much larger than the naive estimate given by the number of jumps required to explore the network multiplied by the average waiting time of the walker at each step [20]. This is a tribute to the extraordinary richness of phenomena brought by the sole departure from a Poisson or discrete-time diffusion process.…”
Section: Discussionmentioning
confidence: 99%
“…The observation that g(t) may have very different moments from f (t), for instance a much larger mean is known under the name of bus paradox, or inspection paradox [19]. In a popular example, one may think of someone arriving at a bus stop and having to wait (mean of g) for a bus much longer than the mean inter-arrival time between two buses (mean of f ).…”
Section: Bias On the Probability Of Backtrackingmentioning
confidence: 99%
See 1 more Smart Citation
“…Collective behaviors of online users have been extensively investigated, which is of great significance for identifying the human communication patterns [1][2][3]. Oliveira et al [4] found the scaling-law in Darwin's and Einstein's correspondence patterns.…”
Section: Introductionmentioning
confidence: 99%